PENGARUH SENAM HAMIL TERHADAP PERSALINAN NORMAL DI KLINIK HANA KASIH MEDAN TAHUN 2015 - Agnes Purba; Dewi Bancin; Diah Novita Sari (Jurnal Reproductive Health, 2016)
Maternal mortality rates occur because of complications of pregnancy or childbirth is hemorrhage, infection is caused by prolonged labor or prolonged second stage and exclamation. Pregnancy exercise serves to strengthen contractions and maintain flexibility of the muscles of the abdominal wall and is associated with childbirth. The purpose of this study was to influence pregnancy exercise on normal childbirth in Klinikhana kasih. This research was conducted in Klinik hana kasih in July 2015. The study was observational study design cross sectional used by case group compared with the control group to determine the effect pregnancy exercise on a normal delivery. The study population was all antenatal mothers who in RSIA and the sample in the study is part of a population of as many as 96 people were divided into two parts, namely the 48mothers who participated gymnastics are referred to as cases and 48 people who did not join gymnastics mom pregnant as control that taken by accidental sampling technique. Analysis of the data by using the chi-square test with a significance value of 5%. The results showed that the process of childbirth in Klinik hana kasih majority of labor is not normal, there is a pregnancy exercise influence on the normal delivery inKlinik hana kasih Year 2015. It is recommended for women in enhanced to follow the pregnancy exercise at least 6 times a week so that the benefits of gymnastics the pregnant mother can feel with maximum and for the Klinik hana kasih in order to make pregnancy exercise into prenatal care program policies, so that pregnant women can experience the benefits of these exercises properly.